CFD STUDY ON THE ABILITY OF A VENTILATED BLADE IN IMPROVING THE SAVONIUS ROTOR PERFORMANCE - Hariyanto, Rudi; Soeparman, Sudjito; Widhiyanuriyawan, Denny; Sasongko, Mega Nur (Journal of Applied Engineering Science, 2018)
This study aims to overview the ability of ventilated blades to improve the performance of the Savonius rotor based on CFD simulation. Rotor performance is analyzed by static torque, pressure profi le, a airfl ow profi le and vortex area. The boundary conditions for all simulations use the assumption that the wind speed is 5 m/s and the environmental pressure is 1 atm or 101325 Pa. The CFD simulation results have strengthen the published experimental results. Ventilation with the 5% gap width of blade diameter (the SV05 model) gives the best performance. Static torque of SV05 model is 23.8% higher than the conventional Savonius (SC) rotor. Based on pressure and airfl ow profi le of CFD simulation results, ventilation on the blade can add the mass fl ow rate of air and make the lift force work early on rotating angle of 0o and 165°. Ventilation on the blade also able to improve the critical condition and vortex area as seen in the SC rotor. This is shown by a static torque from the CFD simulation results. The static torque value of the SV05 rotor are 69% and 73% higher than the SC rotor at the 165° and 0° rotation angle.